The Paleogene mammalian fauna of Santa Rosa, Amazonian Peru - Campbell, Kenneth E. 1943-.; Natural History Museum of Los Angeles County (Los Angeles, Calif. Natural History Museum of Los Angeles County, 2004)
This volume describes most of the known mammalian fauna of the Santa Rosa local fauna of eastern Peru, the first Paleogene vertebrate fauna to be reported from the forested, tropical lowlands of the Amazon Basin. ...The articles are heavily weighted toward taxonomic descriptions of species new to science, but there is also much discussion of the relationships of the new forms and what they might indicate about the evolution of the South American mammalian fauna.--Pref.
The Paleogene Santa Rosa local fauna : introduction / Kenneth E. Campbell, Jr. -- The Paleogene Santa Rosa local fauna of Amazonian Peru / Kenneth E. Campbell, Jr., Carl David Frailey, Lidia Romero-Pittmann -- New Paleogene marsupials from the Amazon Basin of eastern Peru / Francisco J. Goin and Adriana M. Candela -- Paleogene notoungulates from the Amazon Basin of Peru / Bruce J. Shockey, Ralph Hitz, Mariano Bond -- Paleogene rodents from Amazonian Peru / Carl David Frailey and Kenneth E. Campbell, Jr. -- Incisor enamel microstructure of South America's earliest rodents: implications for caviomorph origin and diversification / Thomas Martin -- A possible bat (Mammalia : Chiroptera) from the ?Eocene of Amazonian Peru / Nicholas J. Czaplewski and Kenneth E. Campbell, Jr. -- Enigmatic mammal from the Paleogene of Peru / Franciso J. Goin, [et al.] -- The Santa Rosa local fauna: a summary / Kenneth E. Campbell, Jr.
Includes bibliographical references.
Keywords: Paleontology -- Paleogene; Paleontology -- Peru; Teeth, Fossil